Atividade de ectoenzimas purinérgicas após dano hepático crônico induzido por tioacetamida em ratos wistar e tratados com pentoxifilina - Ebone, Renan da Silva (2023)
The are innumerous hepatotoxic agents that can cause liver injury, but when this damage extends for long periods, it can characterize a chronic profile that makes the patient’s treatment and recuperation difficult. Chronic hepatic diseases (CHD) are a serious worldwide public health problem, which leads to high indices of morbidity and mortality. Due to the difficulties in studying CHD in human beings, experimental injury models are developed in rodents. Thioacetamide (TAA) is a hepatotoxic substance used for this purpose. Each rat, however, demonstrates individual tolerances for the TAA toxicity, as such there is no study in literature that administrates TAA by oral gavage to induce chronic hepatic injury. The nucleotide ATP and its derivatives are released during hepatic injury, acting as cellular signals for lymphocyte response. Ectonucleotidases anchored in its membrane regulate this purinergic signalization, modulating the immune response, so that therapies that affect this purinergic signalization may act as possible therapeutical targets. Besides, pentoxifylline (PTX), is an anti-inflammatory hemorheological drug that may act as a possible antifibrotic agent. In this study an in vivo experiment was made, using 30 Wistar rats, divided into four groups: Group I – Control, Group II – PTX (100mg/kg), Group III – TAA (125mg/kg) and Group IV – TAA (125mg/kg) + PTX (100mg/kg). The chronic hepatic injury occurred by the oral gavage of TAA three times a week for 12 weeks. Groups II and IV animals received PTX orally every day during the 4 last weeks. After this period, the animals were euthanized, and liver and blood were collected for lymphocyte isolation, for hemogram evaluation and serum damage markers as well. In group III animals we observed an increase in AST and a decrease in triglycerides levels in the serum. There was an increase in the total leukocyte cell count in the blood, majorly in neutrophil numbers. There was also a decrease in E-NTPDase activity in liver lymphocytes, a pro-inflammatory profile, while liver membrane ENTPDase we observed an increase in this activity, possibly due to increased ATP signalization released due to cell damage. In blood lymphocytes the ectoenzymes demonstrate increased activities for a regulated immune profile. PTX treatment did not demonstrate alterations in the serum damage markers, suggesting some level of damage reversion. Additionally, the treatment reverted the ectoenzymes activities in liver lymphocytes to physiological levels, differing from those observed in non-treated animals, while in liver membranes the E-NTPDase kept elevated for nucleotides regulation. However, PTX was inefficient to revert the low triglycerides levels in the serum but was able to modulate purinergic signalization during the chronic hepatic injury, which was efficiently induced by our proposed method.